+0  
 
0
282
1
avatar+211 

1.Simplify
A.) |
4-8 |

 

B.) | -4-(-8) |

 

2. Simplify

A.) (x+2)(x-3)

B.)  (x+2)2


more will be put on later

GirlsRbetteR  Sep 11, 2017
 #1
avatar+91215 
+2

A.) | 4 - 8 |   =  l  -4  l  = 4

 

B.) | -4 - (-8) |  =  l  -4 + 8 l    = l 4  l   = 4

 

2. Simplify

A.) (x+2)(x-3)    =   x(x -3)  + 2(x - 3)   =  x^2 - 3x  + 2x - 6   =   x^2  - x  -6

B.)  (x+2)^2   =   ( x + 2) ( x + 2)  =  x(x + 2)  + 2(x + 2)   =  x^2 + 2x + 2x + 4  = x^2 + 4x + 4

 

 

 

cool cool cool

CPhill  Sep 11, 2017

30 Online Users

avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.